Respuesta :

Answer: Option a.

Step-by-step explanation:

To rationalize the expression you need to:

Multiply the numerator and the denominator by the conjugate of the denominator.

The conjugate of the denominator is: [tex]\sqrt{x}-\sqrt{7}[/tex]

Remember that:

[tex](\sqrt[n]{x})^n=x\\\\(\sqrt[n]{x})(\sqrt[n]{y})=\sqrt[n]{xy}[/tex]

Therefore, multiplying the numerator and the denominator by the conjugate of the denominator ([tex]\sqrt{x}-\sqrt{7}[/tex]), you get:

[tex]=\frac{(\sqrt{x})(\sqrt{x}-\sqrt{7})}{(\sqrt{x}+\sqrt{7})(\sqrt{x}-\sqrt{7})}\\\\=\frac{(\sqrt{x})^2-(\sqrt{x})(\sqrt{7})}{(\sqrt{x})^2-(\sqrt{7})^2}\\\\=\frac{x-\sqrt{7x}}{x-7}[/tex]

This is the option a.

ACCESS MORE